1980
DOI: 10.1111/j.1600-0722.1980.tb01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate‐dependent glucose phosphotransferase activity in Streptococcus mitis ATCC 903

Abstract: – A constitutive phosphoenolpyruvate (PEP)‐dependent glucose phosphotransferase system was found in decryptified cells of Strep. mitis. The system displayed saturation kinetics and the apparent Km value for the non‐fermentable analogue 2‐deoxyglucose (2DG) was 0.4 mm. Sodium fluoride inhibited the activity when 2‐phosphoglycerate was used as the energy source instead of PEP, Intact cells accumulated 2DG and also a derivative that behaved chromatographically like 2DG‐6‐phosphate. PEP‐dependent glucose phosphotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Further experiments using pure oral bacteri al strains and subcellular vesicles prepared from these bacteria are necessary to deter mine the precise sugar transport mecha nisms present. Glucose transport occurs by PEP-dependent PTS systems when these bacteria are present as a mixed collection as found in dental plaque [Roberts and Linder, 1980], and the present work shows that in corporation also occurs by other mecha nisms.…”
Section: Effect Of Inhibitorsmentioning
confidence: 74%
See 3 more Smart Citations
“…Further experiments using pure oral bacteri al strains and subcellular vesicles prepared from these bacteria are necessary to deter mine the precise sugar transport mecha nisms present. Glucose transport occurs by PEP-dependent PTS systems when these bacteria are present as a mixed collection as found in dental plaque [Roberts and Linder, 1980], and the present work shows that in corporation also occurs by other mecha nisms.…”
Section: Effect Of Inhibitorsmentioning
confidence: 74%
“…3). 2-Deoxyglucose is non-utilisable by S. mitis and 5. mutans and accu mulates in the cell as the free sugar and as 2-deoxyglucose-6-phosphate [Schachtele and Leung, 1975;Roberts and Linder, 1980]. The saturating part of the 2-deoxyglucose curve may represent an inhibition of uptake due to a build-up of these compounds inside the cell or it may reflect a dynamic equilib rium between uptake and exit reactions.…”
Section: Incorporation Of Glucose Fructose Sucrose and 2-deoxyglucosementioning
confidence: 99%
See 2 more Smart Citations
“…Since that time many at tempts have been made to measure the acidity of den tal plaque following the consumption of sugar or other carbohydrate products, either measuring in vitro [Stephan, 1940[Stephan, , 1944Frostell, 1969;Geddes, 1975] or telemetrically in situ [Graf, 1970;Imfield, 1972;Mortimer et al, 1984], Fluoride has been shown to inhibit acid produc tion in dental plaque [Jenkins, 1959;Geddes and McNee, 1982;Van der Hoeven and Franken, 1984] and has also been shown to inhibit the glycolytic en zyme enolase [Stone and Werkman, 1937], Because of this, fluoride inhibits the glucose uptake into the cell via the phosphoenolpyruvate/phosphotransferase system [Hamilton, 1977;Roberts and Linder, 1980]. In the present study other known glycolytic inhibitors were evaluated for their effect on postchallenge plaque pH.…”
mentioning
confidence: 99%